A sustentabilidade como um novo posicionamento na estratégia de comunicação de empresas brasileiras - Arruda, Nilton Marlucio de (2008)
The main objective of this work is to discuss the methodological proposal that will include in the propaganda strategies of the companies the relationship with some of the stakeholders as well as to think about the possibility and urgency of adopting new methods and better practices based on concepts of the sustainability. To attain it has been analyzed liberature specialized and elaborated field research work with qualitative and quantitative character, starting from a questionnaire to be answered by several publicity and propaganda agencies and also by hundreds of professionals of communication and marketing areas. It must be considered that publicity and propaganda exert astrong power of persuasion and relationship between firms and consumers. This work also has in view to make people think about some examples of changes in publicity language that can already be perceived in campaings held in the last few years relating to their potential to change into methodological marketing